Government research evaluations and academic freedom: a UK and Australian comparison. Issue 2 (23rd February 2017) - Martin-Sardesai, Ann; Irvine, Helen; Tooley, Stuart; Guthrie, James
ABSTRACT: Performance management systems have been an inevitable consequence of the development of government research evaluations (GREs) of university research, and have also inevitably affected the working life of academics. The aim of this paper is to track the development of GREs over the past 25 years, by critically evaluating their adoption in the UK and Australian higher education sector and their contribution to the commodification of academic labour, and to highlight the resultant tensions between GREs and academic freedom. The paper employs a literature-based analysis, relying on publicly available policy documents and academic studies over the period 1985–2010. GREs are a global phenomenon emanating from new public management reforms and while assessments of university research have been welcomed, they have attracted critique based on their design, the manner in which they have been applied, and the unintended consequences of their implementation on academic freedom in particular. Consistent with international research on the impact of GREs, Australian research assessments appear to be undoing the academic freedom that is central to successful research. Further empirical research on the impact of GREs on academics is urgently needed.